Investigasi Keminatan Mahasiswa USS untuk Bisnis melalui Sosial Teknologi agar tercipta Mahasiswa yang Mandiri ( Studi Kasus : Facebook , Instagram ): Investigasi Keminatan Mahasiswa USS untuk Bisnis melalui Sosial Teknologi agar tercipta Mahasiswa yang Mandiri ( Studi Kasus : Facebook , Instagram ) - Diah Triesia Diah (Repository STMIK Prabumulih, 2020)
In the past few years, a lot of business has been done through Social Technology to increase the sales made. Social Technology or Social Media (Facebook, Instagram) is seen by many people as a means of business communication for the community, especially for followers of Social Technology or Social Media accounts (Facebook, Instagram). The objectives to be achieved in this study are to measure how much entrepreneurial spirit is owned by the University of South Sumatra students and to create students who have an entrepreneurial spirit to foster students at the University of South Sumatra to have a business through social technology. As a measure in this study, it has 3 variables, namely Tools, Business and Interests, in this research using an online questionnaire, 201 respondents were obtained. The data from the questionnaire is managed using the SPSS program with the AMOS analysis model. From the Estimate value obtained from each variable as follows, the tools have an estimate value of 0.785, Culture has an estimate value of 0.738, while the key change variable has an estimate value of 0.740, thus proving that the variable can be said to have perfect reliability.